(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
The research aims to know the level of the main variables in the organization under study and to test the impact of the relationship between the core capabilities in enhancing strategic recovery. In order to achieve this, the dimensions of the core capabilities (capabilities, abilities, and resources) were adopted, as well as the dimensions of strategic recovery (speed, apology, and compensation) were adopted. , explanation and clarification, empowerment), and the (Ministry of Electricity) was chosen to test this research, as it is one of the important service sectors and has a vital role in all other sectors and is considered a standard for the quality of life of citizens and contributes greatly to economic and social development. The questionnaire was adopted as a tool in collecting data, The research sample amounted to (155) employees working in the Dhi Qar Electricity Distribution and North Nasiriyah Distribution branches, and through the use of specialized programs such as (SPSS V.27) and other relevant statistical methods such as (Excel) and (AMOS V.27) program, A set of results were reached, the most important of which is (the presence of a significant influence relationship for the core capabilities in strategic recovery in the organization under study), which contributes to confronting events or problems that occur or are possible and finding appropriate solutions to prevent or reduce failure, which enhances strategic recovery and achieves organizational success. The research also presented a number of recommendations, the most important of which is the need for the organization’s management to enhance behaviors that provide an organized guide that contributes to the development and development of the capabilities of individuals and teams and enhances their skills through training courses and workshops, and to strengthen its dynamic capabilities that include a set of definable processes such as service development.